KRITIK SOSIAL DALAM PERTUNJUKAN WAYANG KULIT CENK BLONK LAKON SETUBANDHA PUNGGEL - Pradhananta, Rizki Fajri; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study analyzes and describes how the social criticisms of the Cenk Blonk shadow puppet show especially the Setubandha Punggel play are made by the encoder and are accepted also interpreted by the decoder. The method used in this study is qualitative with descriptive explanatory types. The theory used is the theory of encoding and decoding from Stuart Hall. The theory explains that the 'code' delivered by the encoder to the decoder is not always in a symmetrical position, but there are several reception positions, namely the dominant hegemonic position, the negotiation position, and the position of opposition. From the analysis carried out, most of them revealed that what was conveyed by I Wayan Nardayana in the Cenk Blonk shadow puppet show are in accordance with their thoughts and the existing facts. In other words, most of them are in a dominant hegemonic reception position. Keywords: cenk blonk shadow puppet, setubandha punggel, social criticism, encoding and decoding.